The Potential Return of the German Economy to the «Sick Man Of Europe» Status: Causes, Risks and Possible Implications - ANA-CRISTINA BÂLGĂR (Global Economic Observer)
Around a quarter of a century since Germany was labelled “the sick man of Europe” for the first time, the weak performances the federal economy experienced this year brought the country back to the centre of European and international debates regarding the likely risks posed by the possible lengthening or acceleration of the current cycle of economic decline. While, in the past, the triggers of the first stage of profound contraction experienced by Germany were mainly endogenous (i.e. huge costs required by the completion of the reunification process, a stagnant labour market, an excessive taxation system etc.), at present they are mainly based on the interaction of destabilising forces of exogenous origin: the impact of the Covid-19 pandemic, followed and amplified by the consequences of the Russian-Ukrainian conflict and the resulting energy crisis. Against the background of the recent geopolitical context, our article seeks to provide a comparative analysis (past vs. present) of the two recession phases that Germany went through, revealing both the causes of their occurrence, and the steps taken (or envisaged) by the national decision-makers to help the federal economy recover and to relaunch growth. We will also highlight in our research the potential domino effects for the other European Union Member States, which could be triggered by a lengthy or profound German recession.